Predictors of Severe Neurologic Injury on Ultrasound Scan of the Head and Risk Factor-based Screening for Infants Born Preterm - Beltempo, Marc; Wintermark, Pia; Lemyre, Brigitte; Shalish, Wissam; Martel-Bucci, Andrea; Narvey, Michael; Ng, Eugene H.; Guillot, Mireille; Shah, Prakesh S.; Kanungo, Jaideep; Ting, Joseph; Cieslak, Zenon; et al. (The Journal of pediatrics, 2019)
To identify risk factors for severe neurologic injury (intraventricular hemorrhage grade 3 or greater and/or periventricular leukomalacia) diagnosed by ultrasound scan of the head among infants born at 300-326 weeks of gestation and compare different screening strategies. This was a retrospective cohort study of infants born at 300-326 weeks or >326 weeks of gestation with a birth weight <1500 g admitted to neonatal intensive care units in the Canadian Neonatal Network from 2011 to 2016. Stepwise logistic regression analysis was used to identify significant risk factors and calculate aORs and 95% CIs. Risk factor-based screening strategies were compared. The rate of severe neurologic injury was 3.1% among infants screened (285/9221). Significant risk factors included singleton birth (aOR 1.96, 95% CI 1.35-2.85), 5-minute Apgar <7 (aOR 1.81, 95% CI 1.30-2.50), mechanical ventilation on day 1 (aOR 2.65, 95% CI 1.88-3.71), and treatment with vasopressors on day 1 (aOR 3.23, 95% CI 2.19-4.75). Risk categories were low (no risk factor, 1.2%, 25/2137), moderate (singleton with no other risk factor: 1.8%, 68/3678), and high (≥1 risk factor among 5-minute Apgar <7, receipt of vasopressors or mechanical ventilation on day 1: 5.6%, 192/3408). Screening moderate- to high-risk infants identified 91% (260/285) of infants with severe neurologic injury and would require screening fewer infants (1647 infants per year) than screening all infants <33 weeks of gestation (2064 infants screened per year, 93% [265/285] of cases identified). Risk factor-based ultrasound scan of the head screening among infants born at 30-32 weeks of gestation could help optimize resources better than gestational age based screening.